Applied action development anthropology - Bhowmick, P.K. (Calcutta, 1990)
This book shows the gradual development of the concepts, methods and the expanding horizons of Anthropology in its evolution from the science of man into the science in the service of man. The spirit of harnessing the knowledge of Anthropology to the service of the suffering humanity including the weaker sections of India is the special feature of the book One will find here an analysis of the reports of various committees, Forestry, For est policy, Shifting cultivation, Ex-criminal Tribes of India and their problems. Also, many more aspects of the life of the weaker sections, their health, education, economy, indebtedness, constraints of development as well as problems of the Scheduled Castes, economy, and society of the primitive people of our country constitute the theme of the book.
Keywords: Social Anthropology